Determining how digital marketing strategies affect lifestyle product performance in Chennai - Banu, Haseena; Kumar, K. (The International tax journal, 2026)
This study investigates the influence of digital marketing strategies on the performance of lifestyle products in Chennai. With the increasing use of the internet in business, companies have transformed the way they design, promote, and market their products. The digital environment provides consumers with easy access to detailed information and a wide range of choices. Lifestyle products, which are closely linked to personal preferences, values, and interests, are especially affected by digital marketing practices. Digital marketing strategies such as social media promotion, online advertising, content marketing, and customer engagement activities play a significant role in improving product performance. According to Ilyas et al., digital marketing enhances customer satisfaction, engagement, and loyalty, which are essential for the success of lifestyle products. Effective digital strategies help firms meet customer expectations and make products more attractive and accessible. The study collected data from 120 respondents in Chennai to examine the relationship between digital marketing and consumer behaviour. Statistical tools such as percentage analysis, chi-square tests, and cluster analysis were used. The findings provide valuable insights for businesses to improve digital marketing strategies and increase the market success of lifestyle products.